Wednesday

April 23, 2014

April 23, 2014

Posted by **Kate** on Wednesday, July 27, 2011 at 12:23pm.

a)y + 60x + 294 = -3x^2

b)−(y+1) = (x−4)^2

- Math -
**Henry**, Thursday, July 28, 2011 at 4:03pma. y = -3x^2 -60x - 294.General or STD Form.

h = -b/2a = 60 / -6 = -10.

k = -3(-10)^2 - 60*-10 - 294 = 6.

y = a(x-h)^2 + k,

y = -3(x+10)^2 + 6. Vertex Form.

b. -(y+1) = (x-4)^2,

-y-1 = x^2 - 8x + 16,

-y = x^2 - 8x + 17,

y = -x^2 + 8x - 17,

h = -b/2a = -8 / -2 = 4.

k = -(4)^2 +8*4 - 17 = -1.

y = -(x-4)^2 - 1.

**Related Questions**

Algebra - Please help I can't figure out these two. Express f(x) in the form a(x...

biology - Given the part of the molecule shown below, can the underlined atom ...

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

calculus (gr 12) - Evaluate each of the following. Show all your calculations. a...

Grade 12 Calculus - Evaluate each of the following. Show all your calculations...

College Algebra - Find the equation of the parabola y = ax2 + bx + c that passes...

math - The number 27+200−−−√−−−−...

Product of Roots of Sums of Products of Difference - What is the product of all ...

Product of Roots of Sums of Products of Difference - What is the product of all ...

algebra - Which choice is the equation of a line that passes through the point...